Penginjilan Terhadap Suku Meree – Di Kabupaten Kaimana Melalui Gereja Kemah Injil Papua - Yulian Anouw (Sekolah Tinggi Teologi Jaffray Jakarta, 2022)
This study shows that there are cultural values ​​and worldview concepts of the Meree people who are